Intracellular traffic of the lysine and glutamic acid rich protein KERP1 reveals features of endomembrane organization in Entamoeba histolytica. (26th February 2016) - Perdomo, Doranda; Manich, Maria; Syan, Sylvie; Olivo‐Marin, Jean‐Christophe; Dufour, Alexandre C.; Guillén, Nancy
Summary: The development of amoebiasis is influenced by the expression of the lysine and glutamic acid rich protein 1 (KERP1), a virulence factor involved in Entamoeba histolytica adherence to human cells. Up to date, it is unknown how the protein transits the parasite cytoplasm towards the plasma membrane, specially because this organism lacks a well‐defined endoplasmic reticulum (ER) and Golgi apparatus. In this work we demonstrate that KERP1 is present at the cell surface and in intracellular vesicles which traffic in a pathway that is independent of the ER–Golgi anterograde transport. The intracellular displacement of vesicles enriched in KERP1 relies on the actin‐rich cytoskeleton activities. KERP1 is also present in externalized vesicles deposited on the surface of human cells. We further report the interactome of KERP1 with its association to endomembrane components and lipids. The model for KERP1 traffic here proposed hints for the first time elements of the endocytic and exocytic paths of E. histolytica .